Antitesis Terhadap Yesus Menurut Pandangan Continuanism: Studi Analisis Teks “τὸ τέλειον (To Teleion)” dalam 1 Korintus 13:10 - Andris Kiamani; Aska Aprilano Pattinaja (Sekolah Tinggi Teologi Injili Indonesia (STTII) Yogyakarta, 2024)
The debate between cessationism and continuanism regarding the translation of the phrase τὸ τέλειον (to teleion) continues to this day, through various arguments and interpretations. For this reason, this study aims to analyze the true meaning of the phrase τὸ τέλειον (to teleion) in 1 Corinthians 13:10, which is the basis of the debate between the two groups. Studies that support continuanism have so far interpreted the phrase τὸ τέλειον (to teleion) as a reference to the personality of Jesus, thus making the researcher consider it necessary to comprehensively study to find the true meaning of the phrase τὸ τέλειον (to teleion), using interpretative qualitative methods through the process of exegesis to understand the text in question. This article finds the meaning of the phrase τὸ τέλειον (to teleion) in 1 Corinthians 13:10 does not refer to the personality of Jesus but to the Bible as the Word/Word of God which functions as a medium in shaping spiritual maturity. Thus, the study of the phrase τὸ τέλειον (to teleion) has proven an antithetical interpretation of Jesus' personality according to the view of continuanism.